Barrett's oesophagus patients attending hospital: Baseline clinical, patient history and quality of life data from BOSS and AspECT - Love, S; Reilly, G; Roberts, C; Wise, A; Moayyedi, P; Foy, C; Stokes, C; De Caestecker, J; Attwood, S; Watson, R; Ang, Y; Bhandari, P; et al. (Elsevier, 2016)
From 2005 to 2011 two large UK studies recruited 6,327 evaluable patients with Barrett’s Oesophagus attending hospital clinics. Baseline clinical, patient history and quality of life data was collected prior to randomisation and this rich dataset is the basis for this abstract.